Assessing Intestinal Health in Pigs: Recognizing Unaddressed Areas and Prospective Research Avenues - Marina Patricia Walter; Gabriela Miotto Galli; Alicia Zem Fraga; Aires Santos Silva; Júlio César Vieira Furtado; Pedro João Viera Ascari; Ines Andretta (Veterinary Sciences)
Gut health is crucial for pigs because it affects nutrient absorption, immune function, and growth performance. However, its definition remains unclear, particularly regarding measurable responses in scientific studies. This review critically analyzed studies assessing intestinal health in pigs during the nursery, growing, and finishing phases, focusing on the invasiveness of the applied techniques. Papers published between 2005 and 2023 were searched in PubMed, Web of Science, and Science Direct, resulting in 322 articles. Publications grew at an annual rate of 23%, with 84% of studies conducted in the nursery phase. In the database, 87% of intestinal health assessments were combined with growth performance measures. Semi-invasive methods, such as blood collection, were used in 65% of the studies. Non-invasive measures, such as fecal samples, were analyzed in 39% of the studies, whereas urine (7%) and saliva (0.6%) were used in only a small fraction of the studies. Invasive methods, including intestinal tissue collection, were employed in 89% of studies. Among these, 24% did not specify the euthanasia method or number of pigs euthanized. No significant association was found between invasive and non-invasive methods, limiting the ability to establish clear relationships. Future studies should integrate multiple levels of invasiveness to improve the understanding and reduce reliance on invasive techniques.